Evaluation on the performance of palm oil fuel ash (POFA) as fluid loss reducing agent - Azalan, Siti Aishah (2018)
An attempt to solve the fluid loss problem, numerous additives was introduced in the industry as a fluid loss reducing agent. Thus, this study was conducted to evaluate the effectiveness of the new selected additives to minimize the filtrate loss. Malaysia is the second largest producer of palm oil industry in the world, the production of palm oil caused country to face problems in providing the land for disposal of this industries by-product which has been known as Palm Oil Feul Ash (POFA). Therefore, an alternative was made to eradicate the land disposal by the use of POFA as an additive in water base mud. Following to the American Petroleum Institute (API) the drilling mud was prepared with different concentration of an additives which are 0.5g, 1.0g and 1.5g respectively. The purpose was to study several parameter of rheological properties which are plastic viscosity, yield point, gel strength, filtrate loss and mud cake thickness. The rheological properties was done in both ambient and high pressure high temperature (HPHT). The laboratory experiment was conducted and shows silica oxide was dominant chemical composition of POFA. Subsequently, the rate of fluid loss attains from the mud sample was compared with the commercial fluid loss reducing agent, Hydro Pac-R with average of 13.3ml Basic Mud, 13.7ml POFA and 8.7ml POFA + Hydro Pac-R at ambient while at HPHT 31.6ml Basic Mud, 44.7ml POFA, 32ml POFA + Hydro Pac-R. As a result, POFA seems to improve the filtrate loss by the used of combination concentration formulation between POFA and Hydro Pac-R equally. However, it has been notified that after aging condition all the sample reduced its rheological performance.